Impact of Cause-Related Marketing on Consumer Buying Behavior - Moni, Femy; Reshmy; Joy, Nanet; Roji; Johnson, Cleetus (Ushus Journal of Business Management, 2021)
In recent era, cause-related marketing has become a common term since it emerged in the 1980s. Consumers are the major stakeholders for organisations and their views and satisfaction or agreements are of utmost importance while making strategies. Thus this paper attempts to study the impact of cause-related marketing on consumer buying behaviour. The sample consists of 187 rural consumers in Thrissur district collected with the help of a standardized questionnaire. The data was analysed using descriptive statistics as well as analytical statistics. The paper does not focus on specific product or companies but attempts to get a general idea of consumers. From the analysis it is clear that 38.5 percent of respondents have no idea regarding the term causerelated marketing but unknowingly participate in CRM initiatives. This research paper infers that CRM has a high impact on consumer buying behaviour.